HEADACHES AND THEIR TYPES, PREVENTION AND TREATMENT OF HEADACHES. - Akhmedova Gulchekhra Abdullaevna; Khudoyorova Farangiz (Scholar Express Journals, 2021)
This article tells about one of the most common diseases in human life, headaches and their types, prevention and treatment of migraines, medications used in the treatment, the article also discusses the types of headaches, their causes.
Keywords: Severe, estimate, reasons of headaches, salicin, acetylsalicylic acid, primary headaches, migraine headache, Cluster headaches, sedalgin, pentalgin, spazmoveralgin, 3 groups of drugs